Work accidents in agriculture: a study of Brazilian soybean production - Silva, Paloma Couto Vieira de George [UNESP]; Alves, José Moisés Dos Santos; de Brito, Irineu [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2022)
Soybean cultivation has great economic and social impacts, meaning it offers many job opportunities. Studying the number of accidents in this field is essential for a better understanding of the quality of work related to it. Therefore, the purpose of this article is to verify if, in the field of soybean cultivation, there are correlations between productivity, product price, and the number of accidents, between the years of 1999 and 2018, in Brazil. For that, Pearson’s method was applied, allowing for a bivariate analysis that can quantify a degree of strength between different variables. As a result, it was found that soybean production and price are linearly related to the number of work-related accidents in cultivation. Therefore, it is concluded that, if an increase in price or production occurs, it will lead to an increase in accidents, and the opposite will also happen.
Keywords: Brazil; Linearity; Soybean production; Work accident